What is the place of empirical proton pump inhibitor testing in the diagnosis of gastroesophageal reflux disease? (Description, duration, and dosage) - Vardar, Rukiye; Keskin, Muharrem (Turkish Journal of Gastroenterology, 2017)
Abstract Empirical acid suppression tests that are performed with proton pump inhibitors (PPI) are used to detect both the presence of acid-related gastrointestinal symptoms and gastroesophageal reflux disease (GERD). In comparison to other diagnostic methods, it is non-invasive, easily applicable, and cost-effective in the diagnosis of GERD. In addition to typical reflux symptoms, it can also be used for diagnostic purposes in patients with non-cardiac chest pain (NCCP). If the symptom response is 50% and above when obtained using the PPI test in patients with NCCP, it can be considered as positive and the treatment should be continued sensitivity of the PPI test in patients with typical symptoms of GERD is 27%-89%, while its specificity is 35%-83%. Although there are differences related to the duration and dosage of the PPI test, a significant difference has not been found according to the type of PPI. When PPI test sensitivity and specificity were calculated by cumulatively evaluating the data regarding the PPI test in the literature, a sensitivity of 82.3% and specificity of 51.5% was obtained. It has been found that high doses of PPI were mostly used in studies, and the duration of the median test was 14 days. As a result, the sensitivity of PPI trial test is good, but the specificity is low in the diagnosis of GERD in patients with typical reflux symptoms. Cite this article as: Vardar R, Keskin M. What is the place of empirical proton pump inhibitor testing in the diagnosis of gastroesophageal reflux disease? (Description, duration, and dosage). Turk J Gastroenterol 2017;28(Suppl 1); S12-S15 Full Text Turkish